Effect of including herbal choline in the diet of a dairy herd; a multiyear evaluation - Alfredo Gutiérrez, Alfredo Gutiérrez R.; Sánchez, Carlos; Mendoza, Germán D. (Emirates Journal of Food and Agriculture, 2019)
A linear mixed model and chi-squared tests were used to estimate the effects of the dietary inclusion of herbal choline at 0.071 % of the diet in the entire dairy herd (target dose of 17 g/d in lactating cows) using data from six years in a commercial farm. The feed plant additive (BioCholine) was included in the premix spanning three years (2016-2018) feeding 442 cows average per year and information was compared with the three previous years (2013 – 2015; 424 cows average per year). Energy corrected milk in the period 2016-2018 was increased by 1.57% (p<0.001) compared to years 2013-2016 (36.36 vs. 35.80 kg/d). Fertility in cows during first lactation was improved (P<0.01) with the feed plant additive (45.33 vs. 37.0%). The period feeding herbal choline (2016-2018) showed a reduction (p<0.0001) in abortions (15.65 to 7.29%) and clinical (p<0.005; 12.59 to 6.95%) and subclinical mastitis (p<0.05; 8.65 to 5.22%) and in respiratory disorders (p<0.10; 12.42 to 8.56%) whereas hypocalcaemia incidence was increased (p<0.01) from 1.73 to 6.22%. Total herd replacement was reduced during the years 2016-2018 by 5.73% (p<0.05) without effects in mortality. Inclusion of the plant feed additives containing conjugates of choline improved milk yield, fertility in first lactation cows and important health indicators which help to reduced herd replacement.